Experimental evaluation of the performance and emissions of a direct-injection compression-ignition engine fueled with n-hexanol–diesel blends. (15th October 2021) - Nour, Mohamed; Sun, Zhe; El-Seesy, Ahmed I.; Li, Xuesong
Highlights: The viability of partially replacing diesel with n-hexanol was studied. Pyrolysis of n-hexanol–diesel blends based on TGA was analyzed. The n-hexanol–diesel mixtures improved the fast burn mode. Smoke opacity and NOx were reduced by 58% and 39%, respectively. n-hexanol–diesel blends have great environmental benefits and no engine problems. Abstract: The recent developments in the sustainable production of n-hexanol, in addition to its distinctive physicochemical properties, have encouraged its application in direct-injection compression-ignition (DICI) engines. However, there has been limited research on the substitution of commercial diesel fuel with n-hexanol in DICI engines. This study investigated the impact of blending ratio of an n-hexanol–diesel mixture (up to 50% v/v) on combustion, performance, and emission characteristics of a DICI engine. A single-cylinder 4-stroke air-cooled naturally aspirated diesel engine was used to conduct these investigations. Blending ratios of 10%, 20%, 30%, 40%, and 50% by volume were used in this study without modifying the fuel system. The experiments were performed for two distinct engine settings, namely, at a speed of 900 rpm at 10% engine load and at a speed of 1500 rpm at four engine loads of 25%, 50%, 75%, and 100%. The results demonstrate that the addition of n-hexanol to diesel increased the ignition delay, improved the premixed burn mode, and inhibited the diffusion burn mode. In addition, the total cumulative heat released increased by 9% and 4% for the Hex50 blend (50% n-hexanol and 50% diesel) at engine loads of 75% and 100%, respectively. However, the brake thermal efficiency obtained for commercial diesel fuel was 0.6% greater than that of the n-hexanol–diesel blends. The brake-specific fuel consumption of the Hex50 blend at engine load of 100% was 6.4% higher than that of diesel. NOx emissions and smoke opacity reduced by 26% and 54%, respectively, for Hex50 at an engine load of 100%. Thus, n-hexanol can be used with a maximum substitution rate of 50% in the DICI engines, resulting in substantial environmental benefits and negligible technical issues.